2009
DOI: 10.1603/029.102.0523
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Feeding Preference, and Repellency Associated With Selected Organic Insecticides Against <I>Acrosternum hilare</I> and <I>Euschistus servus</I> (Hemiptera: Pentatomidae)

Abstract: Experiments were conducted to evaluate the toxicity, feeding preference, repellency, and field efficacy associated with the organic insecticides azadirachtin, pyrethrins, and spinosad against two stink bug species, Acrosternum hilare (Say) and Euschistus servus (Say) (Hemiptera: Pentatomidae). Laboratory toxicity bioassays were conducted using treated green bean pods. The conventional pyrethroid lamda-cyhalothrin was included for comparison. A. hilare adults and nymphs were most susceptible to lamda-cyhalothri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…These results are similar to those for neonicotinoid insecticides (Yee 2008). In other insects, however, including house flies, mosquitoes, stinkbugs, and psyllids, there is evidence for repellency or avoidance behavior toward some insecticides (Brown and Pal 1971;Burden 1975;Moore 1977;Pluthero and Singh 1984;Gharalari et al 2009;Kamminga et al 2009). In R. indifferens, females actually spent the most time on spinetoram-treated and control cherries.…”
Section: Discussionsupporting
confidence: 66%
“…These results are similar to those for neonicotinoid insecticides (Yee 2008). In other insects, however, including house flies, mosquitoes, stinkbugs, and psyllids, there is evidence for repellency or avoidance behavior toward some insecticides (Brown and Pal 1971;Burden 1975;Moore 1977;Pluthero and Singh 1984;Gharalari et al 2009;Kamminga et al 2009). In R. indifferens, females actually spent the most time on spinetoram-treated and control cherries.…”
Section: Discussionsupporting
confidence: 66%
“…Pyrethrins, an organic insecticide group derived from Chrysanthemum spp. (Casida 1980), were effective against the green stink bug, Chinavia hilaris (Say), but not the brown stink bug, Euschistus servus (Say), in laboratory bioassays (Kamminga et al 2009). We found that H. halys was susceptible to pyrethrins with 73% lethality after 7 d following 4.5-h exposure to dried residues.…”
Section: Discussionmentioning
confidence: 79%
“…Spinosad has been tested and used for management of many insect pests (Sparks et al 2012), such as Diptera (Burns et al 2001), Lepidoptera (Zhao et al 2002), and Thysanoptera (Eger et al 1998). Kamminga et al (2009) reported that spinosad was as effective as lambda-cyhalothrin in laboratory bioassays against C. hilaris and E. servus. Spinosad was also promising against H. halys in our studies, and this material has demonstrated selectivity against the predatory stink bug, Picromerus bidens (L.) (Mahdian et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentatomidae), formerly known as Acrosternum hilare (Say), is native to North America, where it is broadly distributed across the continent , and has been noted as an economic pest of several crops (e.g., Bundy et al 2000, Greene et al 2001, Atanassov et al 2002, Kamminga et al 2009). In California, C. hilaris is one of a group of hemipteran species that cause direct crop damage to pistachio (Bolkan et al 1984, Rice et al 1985, an exotic crop that has increased greatly in crop acreage and value since the 1980s (Anonymous 2010).…”
mentioning
confidence: 99%